4′‐modified nucleoside analogs: Potent inhibitors active against entecavir‐resistant hepatitis B virus. Issue 4 (25th August 2015) - Takamatsu, Yuki; Tanaka, Yasuhito; Kohgo, Satoru; Murakami, Shuko; Singh, Kamalendra; Das, Debananda; Venzon, David J.; Amano, Masayuki; Higashi‐Kuwata, Nobuyo; Aoki, Manabu; Delino, Nicole S.; Hayashi, Sanae; et al.
<x xml:space="preserve">Abstract</x> Certain nucleoside/nucleotide reverse transcriptase (RT) inhibitors (NRTIs) are effective against human immunodeficiency virus type 1 (HIV‐1) and hepatitis B virus (HBV). However, both viruses often acquire NRTI resistance, making it crucial to develop more‐potent agents that offer profound viral suppression. Here, we report that 4′‐C‐cyano‐2‐amino‐2′‐deoxyadenosine (CAdA) is a novel, highly potent inhibitor of both HBV (half maximal inhibitory concentration [IC50] = 0.4 nM) and HIV‐1 (IC50 = 0.4 nM). In contrast, the approved anti‐HBV NRTI, entecavir (ETV), potently inhibits HBV (IC50 = 0.7 nM), but is much less active against HIV‐1 (IC50 = 1, 000 nM). Similarly, the highly potent HIV‐1 inhibitor, 4′‐ethynyl‐2‐fluoro‐2′‐deoxyadenosine (EFdA; IC50 = 0.3 nM) is less active against HBV (IC50 = 160 nM). Southern analysis using Huh‐7 cells transfected with HBV‐containing plasmids demonstrated that CAdA was potent against both wild‐type (IC50 = 7.2 nM) and ETV‐resistant HBV (IC50 = 69.6 nM for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2xz7tvt1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HBVETV‐RL180M/S202G/M204V</alternatives>), whereas ETV failed to reduce <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2xz7tvvk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HBVETV‐RL180M/S202G/M204V</alternatives> DNA even at 1 μM. Once‐daily peroral administration of CAdA reduced <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2xz7tvw4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HBVETV‐RL180M/S202G/M204V</alternatives> viremia (P = 0.0005) in human‐liver‐chimeric/ <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2xz7tvxp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HBVETV‐RL180M/S202G/M204V</alternatives>–infected mice, whereas ETV completely failed to reduce <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2xz7tvz7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />HBVETV‐RL180M/S202G/M204V</alternatives> viremia. None of the mice had significant drug‐related body‐weight or serum human‐albumin concentration changes. Molecular modeling suggests that a shallower HBV‐RT hydrophobic pocket at the polymerase active site can better accommodate the slightly shorter 4′‐cyano of CAdA‐triphosphate (TP), but not the longer 4′‐ethynyl of EFdA‐TP. In contrast, the deeper HIV‐1‐RT pocket can efficiently accommodate the 4′‐substitutions of both NRTIs. The ETV‐TP's cyclopentyl ring can bind more efficiently at the shallow HBV‐RT binding pocket. Conclusion: These data provide insights on the structural and functional associations of HBV‐ and HIV‐1‐RTs and show that CAdA may offer new therapeutic options for HBV patients. (Hepatology 2015;62:1024‐1036)